2012
DOI: 10.1186/1749-8546-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-mangostin on the expression of anti-inflammatory genes in U937 cells

Abstract: Backgroundα-Mangostin (α-MG) is a main constituent of the fruit hull of the mangosteen. Previous studies have shown that α-MG has pharmacological activities such as antioxidant, antitumor, anti-inflammatory, antiallergic, antibacterial, antifungal and antiviral effects. This study aims to investigate the anti-inflammatory molecular action of α-MG on gene expression profiles.MethodsU937 and EL4 cells were treated with different concentrations of α-MG in the presence of 0.1 ng/mL lipopolysaccharide (LPS) for 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
2
29
0
3
Order By: Relevance
“…Senyawa ini mempunyai berbagai aktifitas farmakologis seperti antioksidan, antitumor, antiinflamasi, antialergi, antibakteri dan antijamur [1,4,5,6,7].…”
Section: Pendahuluanunclassified
“…Senyawa ini mempunyai berbagai aktifitas farmakologis seperti antioksidan, antitumor, antiinflamasi, antialergi, antibakteri dan antijamur [1,4,5,6,7].…”
Section: Pendahuluanunclassified
“…1a). These signaling pathways in turn trigger a multiplicity of transcription factors such as NF-κB (p50/p65) and activator protein 1 (AP-1; c-Fos/c-Jun), which synchronize the stimulation of numerous genes encoding inflammatory mediators [115,118]. Nevertheless, the anti-inflammatory molecular consequence of α-MG is still a matter of debate.…”
Section: Inflammatory Signaling Pathways Of α-Mgmentioning
confidence: 99%
“…Studies [115,116] have demonstrated that α-MG appreciably blocks NO, PGE2, TNF-α and iNOS generation in LPS-triggered RAW 264.7 cells (Fig.1b). PGE2, TNF-α and iNOS are cytokines implicated in inflammatory activities, such as amplified vascular penetrability, vascular dilation and neutrophil chemotaxis [115,117].…”
Section: Inflammatory Signaling Pathways Of α-Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Gamma mangostin dari kulit buah manggis mampu menghambat ekspresi MAPK, NF-kB dan AP-1 dalam makrofag. 17 Hasil penelitian Liu et al 18 secara in vitro alfa mangostin kulit manggis terbukti mampu menurunkan induksi lipopolisakarida (LPS) terhadap sintesi sitokin pro inflamasi TNF-α dan IL-4 melalui penghambatan ekspresi gen oncostatin M pada jalur MAPK pada kultur sel U937.…”
unclassified